Early experience with the Impella pump: Single‐center registry. Issue 8 (8th April 2022) - Zubarevich, Alina; Arjomandi Rad, Arian; Szczechowicz, Marcin; Luedike, Peter; Koch, Achim; Pizanis, Nikolaus; Kamler, Markus; Ruhparwar, Arjang; Weymann, Alexander; Schmack, Bastian
Abstract: Background: With the rapid development of mechanical circulatory support technologies, patients presenting with cardiogenic shock have gained access to various treatment opportunities which were not until recently available. The Impella® pump (Abiomed, Danvers, USA) is a minimally invasive device which provides excellent left ventricular unloading and full circulatory support. The aim of the study was to review our center's experience with Impella® and to analyze the major adverse events associated with the device. Methods: From January 2020 to January 2022, a total of 32 patients underwent Impella® implantation at our center for various indications. Results: The mean age at surgery was 60.3 ± 12.4 years and 9.4% were female. All patients presented with acute cardiogenic shock in INTERMACS Class I (53.1%) and INTERMACS Class II (46.9%). Twenty‐six patients (81.25%) out of the whole cohort have been mobilized on Impella® support. Seventeen patients (53.1%) have been weaned from the Impella® support and 10 patients (31.3%) have been bridged to durable LVAD. The median time on Impella® was 7 days (IQR 5.0–11.0). 30‐day mortality was 37.5%, with 56.25% survival until hospital discharge. Only one patient developed vascular complications consisting of arm hypoperfusion. There were no cases of stroke on Impella® support. Conclusion: The Impella® axial‐flow pump seems an appropriate therapeutic option for patients with acute cardiogenic shock requiring partial or full hemodynamic support. It also provides sufficient left ventricular unloading to allow full mobilization and neurological assessment of the patients. Furthermore, Impella® offers a high rate of myocardial recovery. Abstract : Impella® axial‐flow pumpis a feasible treatment option with favourable complications rates for patients in acute cardiogenic shock requiring partial or full haemodynamic support. The pump provides sufficient left ventricular unloading with full mobilisation and neurological assessment of patients and potential for organ recovery prior to durable LVAD implantation. Furthermore, the device may lead to high rate of myocardial recovery resulting in full weaning off mechanical circulatory support.